Evaluation of two novel leptospiral proteins for their interaction with human host components. Issue 5 (28th April 2016) - Silva, Lucas P.; Fernandes, Luis G. V.; Vieira, Monica L.; de Souza, Gisele O.; Heinemann, Marcos B.; Vasconcellos, Silvio A.; Romero, Eliete C.; Nascimento, Ana L. T. O.
Abstract : Pathogenic species of the genus Leptospira are the etiological agents of leptospirosis, the most widespread zoonosis. Mechanisms involved in leptospiral pathogenesis are not well understood. By data mining the genome sequences of Leptospira interrogans we have identified two proteins predicted to be surface exposed, LIC10821 and LIC10064. Immunofluorescence and proteinase K assays confirmed that the proteins are exposed. Reactivity of the recombinant proteins with human sera has shown that rLIC10821, but not rLIC10064, is recognized by antibodies in confirmed leptospirosis serum samples, suggesting its expression during infection. The rLIC10821 was able to bind laminin, in a dose-dependent fashion, and was called Lsa37 (leptospiral surface adhesin of 37 kDa). Studies with human plasma components demonstrated that rLIC10821 interacts with plasminogen (PLG) and fibrinogen (Fg). The binding of Lsa37 with PLG generates plasmin when PLG activator was added. Fibrin clotting reduction was observed in a thrombin-catalyzed reaction, when Fg was incubated with Lsa37, suggesting that this protein may interfere in the coagulation cascade during the disease. Although LIC10064 protein is more abundant than the corresponding Lsa37, binding activity with all the components tested was not detected. Thus, Lsa37 is a novel versatile adhesin that may mediate Leptospira Ã¢ÂÂhost interactions. Abstract : We describe a novel protein in Leptospira interrogans that is most probably involved in hostÃ¢ÂÂpathogen interactions.